Proceedings of the 6th ACM Conference on Bioinformatics, Computational Biology and Health Informatics 2015
DOI: 10.1145/2808719.2808720
|View full text |Cite
|
Sign up to set email alerts
|

Discovering de facto diagnosis specialties

Abstract: In health care institutions, medical specialty information may be lacking or inaccurate, in part because there is no official code to express such specialties. Diagnosis histories offer information on which medical specialties may exist in practice, regardless of whether they have official codes. We refer to such specialties that are predicted with high certainty by diagnosis histories de facto diagnosis specialties. The objective of our research is to discover de facto diagnosis specialties under a general di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…A preliminary version of the de facto diagnosis specialty discovery portion of this work was reported at the 6th ACM Conference on Bioinformatics, Computational Biology, and Health Informatics . The research reported in the current paper extends the prior work and includes comprehensive studies of both recognizing and discovering de facto diagnosis specialties.…”
Section: Introductionmentioning
confidence: 73%
“…A preliminary version of the de facto diagnosis specialty discovery portion of this work was reported at the 6th ACM Conference on Bioinformatics, Computational Biology, and Health Informatics . The research reported in the current paper extends the prior work and includes comprehensive studies of both recognizing and discovering de facto diagnosis specialties.…”
Section: Introductionmentioning
confidence: 73%